Retraction Note: Use of Prayer by Parents in Pediatric Emergency Department Patients - Çaksen, Hüseyin (Journal of Child Science, 2022)
An investigation by the publisher found a number of articles, including this one, published in Journal of Child Science in Volume 12, Number 01, e90–e91, on September 19, 2022 (DOI: 10.1055/s-0042-1757141), with a number of concerns, including but not limited to undeclared conflicts of interest and manipulated peer review procedures. As a result, the publisher has retracted and removed this article.